Improvement of handling properties of naproxen using ordered mixing method - Mateusz Przywara; Karolina Maria Leś; Marta Piwódzka; Marcin Chutkowski; Ireneusz Opaliński (Polish Pharmaceutical Society, 2024)
Study subject: A significant share of the raw materials used in pharmaceutical production are bulk materials. One of the key parameters affecting the quality of the manufacturing process and pharmaceutical product as well as determining the processing properties of raw materials in the manufacturing of solid drug forms is the flowability of the bulk powders. Flowability is important in the case of volumetric dosage of powder materials, in the production of tablets, capsules or granules. Research Objective: The purpose of this study was to develop a method for improving the flowability of naproxen using the ordered mixing process in the high-speed mixer-granulator. Naproxen was mixed with fumed silica. The process of adjusting interactive mixing parameters, i.e., the rotation speed of the main stirrer and the side stirrer, was performed and their effect on the flowability of naproxen was evaluated. A detailed analysis of the effect of process time on the tested material flowability was also carried out. Material and methods: In this study naproxen was doped with nanometric hydrophilic fumed silica under the trade name AEROSIL® 200. Interactive mixing was performed in the high-speed mixer-granulator. The flowability of the obtained mixtures was evaluated based on the selected Carr indices. Results: A reduction of about 20 deg in the angle of repose and the compressibility index by about 20% and an increase of about 8 deg in the angle of difference compared to the starting raw material were obtained. Significant improvement in the flowability of naproxen was obtained already after 5 min of mixing at the main stirrer speed of 150-300 rpm and side stirrer speed of 300-1500 rpm. Conclusions: The applied method makes it possible to reduce the amount of lubricant used compared to traditional mixing methods that involve mainly tumbling blenders. Improved flowability has a beneficial effect on further stages of production of pharmaceuticals containing naproxen, i.e. mixing with other components of the drug, tableting or encapsulation.